The Effect Of Treatment Protocol and Implant Dimensions on Primary Stability Utilizing Resonance Frequency Analysis - Thair Abdul Lateef (College of Dentistry/ University of Baghdad, 2017)
ABSTRACT Background: According to Branemark's protocol, the waiting period between tooth extraction and implant placement is 6-8 months; this is the late placement technique. Achieving and maintaining implant stability are prerequisites for a dental implant to be successful. Resonance Frequency Analysis (RFA) is a noninvasive diagnostic method that measures implant stability. The aim of this study was to investigate the influence of treatment protocol and implant dimensions on primary implant stability utilizing RFA. Materials and methods: This study included 63 Iraqi patients (37 male, 26 female; ranging 22-66 years). According to treatment protocol, the sample was divided into 2 groups; A (delayed) & B (immediate). Dental implants were inserted and the implant stability quotient (ISQ) measures for primary stability documented by Osstell device. Results: For both groups fixtures introduced in the mandible showed a higher stability (74 and 71.85) respectively and was lower in maxilla. The mean primary stability of group A was 70.21 (ranged from 51-83), while for group B was 68.55 (46.5-81). Conclusion: primary stability influencing osseointegration and subsequent long term success. It was higher in association with delayed implant placement, mandible, and increased implant diameters.